Determinan Penting Stock Return pada Jakarta Islamic Index (JII) ditinjau dari Faktor Makroekonomi - Hesniati Hesniati; Verren Calystania; Jessica Novia; Veni Sisca; Vira Vira; Stephanie Stephanie (Penerbit Goodwood, 2023)
Purpose: This study analyzes the effect of macroeconomic factors, including inflation, interest rates, exchange rates, and money supply, on the stock return rate of the Jakarta Islamic Index (JII). Methodology/approach: The data in this study were processed using the multiple linear regression approach in SPSS 26.0. The sample includes monthly data on the Jakarta Islamic Index (JII) Sharia index for ten years from January 2013 to January 2023. Results: The analysis results prove that the exchange rate and inflation have a significant negative effect on JII stock returns. In contrast, the interest rate and money supply do not have a significant relationship with stock returns. Limitations: A low adjusted R-squared value indicates that the independent variables can only explain the limited scope of the dependent variable. Thus, it can be concluded that additional variables are required to be included in this investigation. Contribution: This study is expected to provide a reference for further research. In addition, using one of the Sharia indices in this study is expected to provide a new view to novice investors that not only shares of conventional companies are traded but also shares of Sharia companies. It is hoped that this study’s results will also help investors prospect JII stock returns to help them find the best investment decision. Novelty: Many previous studies have conducted research on stock prices using the Jakarta Islamic Index (JII). However, research on stock returns using this index has not been found.